A phase 1/pharmacokinetic study of sunitinib in combination with highly active antiretroviral therapy in human immunodeficiency virus‐positive patients with cancer: AIDS Malignancy Consortium trial AMC 061. Issue 8 (28th January 2014) - Rudek, Michelle A.; Moore, Page C.; Mitsuyasu, Ronald T.; Dezube, Bruce J.; Aboulafia, David; Gerecitano, John; Sullivan, Ryan; Cianfrocca, Mary E.; Henry, David H.; Ratner, Lee; Haigentz, Missak; Dowlati, Afshin; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The treatment of non–acquired immunodeficiency syndrome‐defining cancers may be complicated by drug interactions between highly active antiretroviral therapy (HAART) and chemotherapy. This trial is the first by the AIDS Malignancy Consortium to assess targeted therapies and HAART in human immunodeficiency virus‐positive patients (ClinicalTrials.gov identifier: NCT00890747). METHODS In a modified phase 1 study of sunitinib, patients were stratified into 2 treatment arms based on whether they were receiving therapy with ritonavir, a potent CYP3A4 inhibitor. Patients in treatment arm 1 (non‐ritonavir HAART) received standard sunitinib dosing (50 mg/day). Treatment arm 2 (ritonavir‐based HAART) used a phase 1, 3 + 3 dose escalation design (from 25 mg/day to 50 mg/day). Cycles were comprised of 4 weeks on treatment followed by a 2‐week break (6 weeks total). The pharmacokinetics of sunitinib and its active metabolite (N‐desethyl sunitinib) were assessed. RESULTS Nineteen patients were enrolled and were evaluable. Patients on treatment arm 1 tolerated treatment with no dose‐limiting toxicity observed. In treatment arm 2, a dose‐limiting toxicity was experienced at a dose of 37.5 mg, and an additional 3 of 5 patients experienced grade 3 neutropenia (toxicity graded as per National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]), an uncommon toxicity of sunitinib. No patient achieved a response, but 10 patients had stable disease, including 8 with prolonged disease stability. Efavirenz, a potent inducer of CYP3A4, resulted in increased exposure of N‐desethyl sunitinib, whereas ritonavir caused decreased exposure of the metabolite. Hand‐foot syndrome was associated with higher steady‐state trough concentrations of sunitinib. CONCLUSIONS Patients receiving non–ritonavir‐based HAART regimens tolerated standard dosing of sunitinib. Patients receiving ritonavir‐based therapy who were treated with a dose of 37.5 mg/day experienced higher toxicities. Dose reductions of sunitinib to 37.5 mg may be warranted in patients receiving ritonavir. Cancer 2014;120:1194–1202. © 2014 American Cancer Society.